2010
DOI: 10.4049/jimmunol.0902669
|View full text |Cite
|
Sign up to set email alerts
|

miR-126 Is Downregulated in Cystic Fibrosis Airway Epithelial Cells and Regulates TOM1 Expression

Abstract: Material Supplementary 9.DC1http://www.jimmunol.org/content/suppl/2010/01/13/jimmunol.090266References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(174 citation statements)
references
References 45 publications
8
163
0
3
Order By: Relevance
“…SLC7A5 expression was not detectable in normal lung tissue, which is in accordance with previous observations (Supplementary Fig. 3A, inset, and [12]). In contrast, the SCLC tumors tested positive for SLC7A5 protein expression -in fact, 8 tumors contained more than 70% SLC7A5-positive cells.…”
Section: Slc7a5 Is a Direct Target Of Mir-126supporting
confidence: 82%
See 1 more Smart Citation
“…SLC7A5 expression was not detectable in normal lung tissue, which is in accordance with previous observations (Supplementary Fig. 3A, inset, and [12]). In contrast, the SCLC tumors tested positive for SLC7A5 protein expression -in fact, 8 tumors contained more than 70% SLC7A5-positive cells.…”
Section: Slc7a5 Is a Direct Target Of Mir-126supporting
confidence: 82%
“…Interestingly, in SCLC cells miR-126 overexpression does not suppress PLK2 expression, even though PLK2 was shown to be a bona fide target for miR-126 in CBF acute myeloid leukemia (AML) cells. A similar observation can be made for TOM1, which is targeted by miR-126 in CF airway epithelium cells, but not in MCF7 cells [4,12]; or for SPRED1, which is targeted in HUVEC cells, but not in AML cell lines [5,13]. It is presently unclear how certain target mRNAs are presented to, and others are protected from miR-126 in these experimental setups, but the resulting target selectivity could contribute to the varied functions of miR-126.…”
Section: Discussionmentioning
confidence: 83%
“…miR-126 is relevant in many tumors, and studies have shown that miR-126 is significantly downregulated in gastric cancer tissues (Feng et al, 2010), non-small cell lung cancer cell lines (Zhu et al, 2012), prevalent diabetes mellitus (Zampetaki et al, 2010), cystic fibrosis airway epithelial cells (Oglesby et al, 2010), human breast cancer (Zhu et al, 2011), invasive ductal adenocarcinoma (Hamada et al, 2011), and cervical cancer tissues (Wang et al, 2008), as compared with relevant normal tissues. Using qRT-PCR analysis, we found that the expression of miR-126 in cervical cancer tissues was significantly decreased compare to that in normal cervical tissues, consistent with a previous report (Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-126 expression has been shown to be downregulated in cystic fibrosis (CF) versus non-CF airway epithelial cells, which correlated with a reciprocal increase in the expression of its predicted protein target TOM1 (target of Myb1) [133]. The authors suggest that TOM1 may play an antiinflammatory role in CF lung and postulate that its increased expression may be an attempt to compensate for the high proinflammatory burden in this condition.…”
Section: Other Respiratory Diseasesmentioning
confidence: 94%